Analisa Kepentingan Tiongkok Melalui Belt and Road Initiative (BRI) dalam Pembangunan Infrastruktur di Sulawesi Utara 2017-2022 - Amaliyah, Firda; Muhaimin, Ramdhan (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The Belt and Road Initiative (BRI) is an international economic trade route connecting Asia, Africa and Europe, consisting of around 60 countries. BRI aims to improve the world economy and create new trade routes to increase business opportunities in terms of exports, imports and investment for China. This research aims to reveal China's national interests behind investments or loans provided through BRI in infrastructure cooperation in North Sulawesi. The projects included in this collaboration are Bitug Port, development of Bitung Port, and construction of the Manado-Bitung Toll Road. The researcher used a qualitative method in which the study used a literature study method, which allowed the author to carry out fact-based analysis of the data found during the research. This research results in the conclusion that the cooperation carried out by China through the BRI with Indonesia is in China's national interests, namely helping to improve the economy through easy exports and imports and affordable infrastructure development in North Sulawesi.